Images of Mothers of Classical and Hellenistic Sparta - Myszkowska-Kaszuba, Magdalena (Polskie Towarzystwo Filologiczne i Uniwersytet Wrocławski, 2019)
This paper is a summary of a PhD dissertation that was written as part of the Project “The Eastern Mediterranean from the 4th Century BC until Late Antiquity”. The project was coordinated by Professor Krzysztof Nawotka (Uniwersity of Wrocław) and ran between 2011 and 2015 within the International PhD Projects Programme of the Foundation for Polish Science, co-financed by the European Union from the Regional Development Fund within the framework of Measure 1.2 “Strengthening the Human Potential within the Science Sector”, part of the Operational Programme “Innovative Economy”. The dissertation was supervised by Professor Ryszard Kulesza (University of Warsaw) and Professor Christopher Tuplin (University of Liverpool) and defended at the Department of History, University of Wrocław, on January 29, 2019. The dissertation was reviewed by Professor Danuta Musiał (Nicolaus Copernicus University, Toruń).
Keywords: Classical Sparta; Hellenic Sparta; images of mothers